The Influence Of K-Pop Fanatism on The Social Behavior of High-Class Students - Fauziah, Siti Pupu; Castara, Tiara Intan; Gunadi, Gugun (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
The decline in social behaviour among elementary school students makes them individualistic, have a high level of selfishness, and have a decreased sense of empathy. This is based on several factors that exist within them. One of them is being a fan who is quite fanatical about one object, namely K-pop culture. This research aims to find out how much influence K-pop fanaticism has on social behaviour. Data was collected through a questionnaire completed by high-class students at SDN Nyangkowek 02, Cicurug District, Sukabumi Regency. This research method uses quantitative correlation methods. The research results obtained were that there was an influence of 4.4% between variables. So, it can be concluded that this research provides information regarding the influence of K-Pop fanaticism on social behaviour in high-class students with a percentage of 4.4%.